The KIDNEYCODE Program: Diagnostic Yield and Clinical Features of Individuals with CKD. Issue 5 (26th May 2022) - Lieberman, Kenneth V.; Chang, Alexander R.; Block, Geoffrey A.; Robinson, Kristina; Bristow, Sara L.; Morales, Ana; Mitchell, Asia; McCalley, Stephen; McKay, Jim; Pollak, Martin R.; Aradhya, Swaroop; Warady, Bradley A.
Key Points: Positive findings were detected in 234 out of 859 (27%) individuals associated with Alport syndrome ( n =209) and other CKDs. For the 248 individuals who had kidney biopsies, a molecular diagnosis was returned for 49 (20%). These findings support the need to improve access to genetic testing for patients with CKD. Visual Abstract: Abstract : Background: Despite increasing recognition that CKD may have underlyi ng genetic causes, genetic testing remains limited. This study evaluated the diagnostic yield and phenotypic spectrum of CKD in individuals tested through the KIDNEYCODE sponsored genetic testing program. Methods: Unrelated individuals who received panel testing (17 genes) through the KIDNEYCODE sponsored genetic testing program were included. Individuals had to meet at least one of the following eligibility criteria: eGFR ≤90 ml/min per 1.73m 2 and hematuria or a family history of kidney disease; or suspected/biopsy-confirmed Alport syndrome or FSGS in tested individuals or relatives. Results: Among 859 individuals, 234 (27%) had molecular diagnoses in genes associated with Alport syndrome ( n =209), FSGS ( n =12), polycystic kidney disease ( n =6), and other disorders ( n =8). Among those with positive findings in a COL4A gene, the majority were in COL4A5 ( n =157, 72 hemizygous male and 85 heterozygous female individuals). A positive family history of CKD, regardless of whether clinical features were reported, was more predictive of a positive finding than was the presence of clinical features alone. For the 248 individuals who had kidney biopsies, a molecular diagnosis was returned for 49 individuals (20%). Most ( n =41) individuals had a molecular diagnosis in a COL4A gene, 25 of whom had a previous Alport syndrome clinical diagnosis, and the remaining 16 had previous clinical diagnoses including FSGS ( n =2), thin basement membrane disease ( n =9), and hematuria ( n =1). In total, 491 individuals had a previous clinical diagnosis, 148 (30%) of whom received a molecular diagnosis, the majority (89%, n =131) of which were concordant. Conclusions: Although skewed to identify individuals with Alport syndrome, these findings support the need to improve access to genetic testing for patients with CKD—particularly in the context of family history of kidney disease, hematuria, and hearing loss.